The Palgrave Handbook of Climate History
XXV, 656 p. 80 illus.
Keywords: This handbook offers the first comprehensive, state-of-the-field guide to past weather and climate and their role in human societies. Bringing together dozens of international specialists from the sciences and humanities, this volume describes the methods, sources, and major findings of historical climate reconstruction and impact research. Its chapters take the reader through each key source of past climate and weather information and each technique of analysis; through each historical period and region of the world; through the major topics of climate and history and core case studies; and finally through the history of climate ideas and science. Using clear, non-technical language, The Palgrave Handbook of Climate History serves as a textbook for students, a reference guide for specialists and an introduction to climate history for scholars and interested readers.